2020
DOI: 10.7717/peerj.9045
|View full text |Cite
|
Sign up to set email alerts
|

A new aggressive xenograft model of human colon cancer using cancer-associated fibroblasts

Abstract: Background Colorectal cancer is the second leading cause of cancer death. Almost half of the patients present recurrence within 5 years after the treatment of the primary tumor, the majority, with metastasis. On the other hand, in the search for new animal models that simulate metastatic cancer, it has been suggested that fibroblasts immersed in the peritumoral stroma (cancer-associated fibroblasts (CAFs)), play a relevant role in the development of cancer. The objective of this study was to identify an adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Yang et al [ 46 ] observed lung metastasis by subcutaneously injecting the two cell types into mice. Wang et al [ 47 ] treated HCT116 cells with CM from MRC-5 cells overexpressing miR-146a-5p and miR-155-5p and injected HCT116 cells through the tail vein of nude mice to observe lung metastasis, while Fernando-Macias et al [ 48 ] injected CAFs and HT29 cells into the pancreatic head of nude mice to observe the effect of CAFs on tumor metastasis. This study found that when human CAFs were combined with human tumor cells, liver and lung metastases were more obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [ 46 ] observed lung metastasis by subcutaneously injecting the two cell types into mice. Wang et al [ 47 ] treated HCT116 cells with CM from MRC-5 cells overexpressing miR-146a-5p and miR-155-5p and injected HCT116 cells through the tail vein of nude mice to observe lung metastasis, while Fernando-Macias et al [ 48 ] injected CAFs and HT29 cells into the pancreatic head of nude mice to observe the effect of CAFs on tumor metastasis. This study found that when human CAFs were combined with human tumor cells, liver and lung metastases were more obvious.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that some molecules expressing on CAF, including WNT2 (Huang et al 2022 ), WNT5a (Hirashima et al 2021 ), CLEC3B (Zhu et al 2019 ), IFNAR1 (Cho et al 2020 ), IL-34 (Franzè et al 2020 ), miR-1246 (Si et al 2021 ), and FAP (Yuan et al 2021 ), play an important role in the development of CRC, and are expected to become a target for anticancer therapy. And many models have been established to study CAF in CRC, such as 3D model of tumor tissue in vitro to simulate the physiological function of cells in vivo (Chen et al 2020 ), in vitro co-culture model of patient-derived organ-like organ (PDO) and patient-derived CAF (Luo et al 2021 ; Naruse et al 2021 ), and mouse xenotransplantation model co-injected with CAF and CRC cell line (Fernando-Macías et al 2020 ). These models are helpful to investigate the functions of various subtypes of CAF, and find the therapy strategies targeting CAF in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that some molecules expressing on CAF, including WNT2 14 , WNT5a 15 , CLEC3B 5 , IFNAR1 16 , IL-34 17 , miR-1246 18 , and FAP 19 , play an important role in the development of CRC, and are expected to become a target for anticancer therapy. And there are many models have been established to study CAF in CRC, such as 3D model of tumor tissue in vitro to simulate the physiological function of cells in vivo 20 , in vitro co-culture model of patient-derived organ-like organ (PDO) and patientderived CAF 21,22 , and mouse xenotransplantation model co-injected with CAF and CRC cell line 23 . These models are helpful to investigate the functions of various subtypes of CAF, and nd the therapy strategies targeting CAF in CRC.…”
Section: Introductionmentioning
confidence: 99%